Introducing professionalism and medical ethics in undergraduate integrative medical curriculum through a four-dimensional model - Ihab S. Atta (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: To develop a method for designing the ethics and professionalism compatible with the integrative medical curriculum. So that the insertion of ethics and professionalism should start from the initial stages of the integrative program in an indirect manner through student-centered activities, passing through introducing some ethical topics that are appropriate for each module, developing a condensed module at the beginning of the clinical stage, and ended by developing a practical course in the internship period. In this way, a four-dimensional model to present ethics and professionalism has been introduced. MATERIALS AND METHODS: A questionnaire was conducted for students (230 students) and faculty (65 faculty members) to find out the current situation of ethics and professionalism and the extent of their aspiration and passion for developing it. RESULT: The result revealed low student and faculty satisfaction with the ethics presentation in the current situation. Educational objectives and outcomes have been developed, and the appropriate teaching model was selected, selecting the main topics, and mapped through a four-dimensional model and assigning the appropriate assessment tools and evaluation mechanisms. CONCLUSION: This model ensures that the student learns ethics and professionalism and breathes its rules from the beginning of his academic studies. In this way, the student will be able to practice those rules in an automatic and spontaneous manner without having any difficulty in practicing them. In addition, this model helps in breaking down the barriers between faculty members, the basic and clinical sciences, and medical departments which are one of the most important goals of integrative medical education.